2019
DOI: 10.1136/bmjsem-2019-000521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a structured, group-based running programme on clinical, cognitive and social function in youth and adults with complex mood disorders: a 12-week pilot study

Abstract: BackgroundIndividuals with mood disorders often report lingering health-related quality of life (HRQOL) and social and cognitive impairments even after mood symptoms have improved. Exercise programmes improve mood symptoms in patients, but whether exercise improves functional outcomes in patients with difficult-to-treat mood disorders remains unknown.DesignWe evaluated the impact of a 12-week structured running programme on cognitive, social and quality-of-life outcomes in participants with difficult-to-treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Three studies investigated the impact of exercise on objective cognitive function, including aerobic exercise programs (Keating et al, 2019; Olson et al, 2017) and high‐intensity interval training (Lee et al, 2019). A single‐arm trial showed that a 12‐week structured running group, Team Unbreakable, which occurred twice per week and gradually increased to a distance of 5 km, produced significant improvement in two tasks of processing speed and attention capacity, out of 18 cognitive tasks in total (Keating et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies investigated the impact of exercise on objective cognitive function, including aerobic exercise programs (Keating et al, 2019; Olson et al, 2017) and high‐intensity interval training (Lee et al, 2019). A single‐arm trial showed that a 12‐week structured running group, Team Unbreakable, which occurred twice per week and gradually increased to a distance of 5 km, produced significant improvement in two tasks of processing speed and attention capacity, out of 18 cognitive tasks in total (Keating et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the impact of exercise on objective cognitive function, including aerobic exercise programs (Keating et al, 2019; Olson et al, 2017) and high‐intensity interval training (Lee et al, 2019). A single‐arm trial showed that a 12‐week structured running group, Team Unbreakable, which occurred twice per week and gradually increased to a distance of 5 km, produced significant improvement in two tasks of processing speed and attention capacity, out of 18 cognitive tasks in total (Keating et al, 2019). A second RCT showed that an 8‐week aerobic exercise intervention, consisting of three 30–45‐min training sessions per week maintained at moderate intensity, produced significantly large improvements in reaction time ( η = 0.13), and an increase in N2 amplitude ( η = 0.13) reflecting greater cognitive control processes, compared to placebo exercise (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations